2023
DOI: 10.1002/mus.27848
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive ventilation usage and adherence in children and adults with Duchenne muscular dystrophy: A multicenter analysis

Abstract: Introduction/Aims: Non-invasive ventilation (NIV) is routinely prescribed to support the respiratory system in Duchenne muscular dystrophy (DMD) patients; however, factors improving NIV usage are unclear. We aimed to identify predictors of NIV adherence in DMD patients.Methods: This was a multicenter retrospective analysis of DMD patients prescribed NIV and followed at (1) The Hospital for Sick Children, Canada; (2) Rady Children's

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This was consistent with a prior report that median age at loss of ambulation was signi cantly earlier in Hispanic boys than a non-Hispanic white population 43 . Another study reported that Hispanic ethnicity was signi cantly associated with higher nightly use of non-invasive ventilation in DMD 27 . We were concerned that differences in FVC% decline in Hispanic and non-Hispanic boys might have re ected a different level of care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was consistent with a prior report that median age at loss of ambulation was signi cantly earlier in Hispanic boys than a non-Hispanic white population 43 . Another study reported that Hispanic ethnicity was signi cantly associated with higher nightly use of non-invasive ventilation in DMD 27 . We were concerned that differences in FVC% decline in Hispanic and non-Hispanic boys might have re ected a different level of care.…”
Section: Discussionmentioning
confidence: 99%
“…These features of the cohort enabled analysis of the impact of newer therapies and Hispanic ethnicity on DMD progression. DMD disease progression was measured serially by forced vital capacity percent of predicted (FVC%), a widely used pulmonary function test that is a prognostic factor for DMD outcomes such as loss of ambulation and mortality 13,18,[24][25][26][27] . The mixed effect linear regression model of FVC% was partially validated by redevelopment in an overlapping but slightly larger cohort with one and half years of additional follow up and 19% more FVC% measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Although NIV has proven to show positive outcomes in children with NMD, adherence to NIV remains an issue. Hurvitz and Sunkonkit et al [41], have shown through a retrospective analysis of data collected from three major centers caring for fifty-nine children with DMD and on NIV. They found that those who were older, had a lower FVC, and those who were not on deflazacort were associated with adherence to NIV, but were not statistically significant when included in the multivariable analysis.…”
Section: Non-invasive Ventilatory (Niv) Supportmentioning
confidence: 99%
“…Several studies have shown that NIV adherence is often poor in patients with neuromuscular diseases. Rautemaa et al found that 72% of patients with type 1 myotonic dystrophy scarcely used NIV (<5 h per 24 h) [ 5 ], although a recent multicenter retrospective analysis demonstrated that NIV was used more than 70% of nights with an average nightly usage of 7 h by patients with Duchenne muscular dystrophy, particularly by older subjects [ 6 ].…”
Section: Introductionmentioning
confidence: 99%